Gizi Seimbang Balita untuk Tumbuh Kembang Optimal - Nadiah Safitri, Lailatif; Sriyani, Endang; Haerani; Nur Khayati, Yulia (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Toddlers balanced nutrition is very important to support optimal growth and development. A balanced diet includes various types of foods, such as carbohydrates, proteins, fats, vitamins, and minerals, in amounts that suit the child's needs. The aim of this community service is in order to mothers can understand about toddlers balanced nutrition. The Community Service Method implemented by 3 stages; the First Stage is the preliminaries stage by conducting a problem assessment and collaboration with partners. The Second Stage is to provide counseling about toddlers balanced nutrition to their mothers on May 7, 2025. The activity began by giving pretest questions to determine toddler mothers’ knowledge level before being given counseling. The Third Stage is conducted an evaluation by giving posttest questions for toddler’s mothers to determine their knowledge level about toddler balanced nutrition after being given counseling. The Community Service result found that this activity was attended by 17 toddler’s mothers and 1 village midwife. The results showed that there was an increase of toddler’s mother knowledge about toddler balanced nutrition after given Health education. It is hoped that health workers will increase health education about toddlers balanced nutrition to the community in order to improve toddler growth and development.   Abstrak Gizi seimbang pada balita sangat penting untuk mendukung pertumbuhan dan perkembangan optimal. Pola makan yang seimbang mencakup berbagai jenis makanan, seperti karbohidrat, protein, lemak, vitamin, dan mineral, dalam jumlah yang sesuai dengan kebutuhan anak. Tujuan pengabdian masyarakat ini adalah agar ibu balita memahami tentang gizi seimbang pada balita. Metode Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama yaitu tahap persiapan dengan melakukan pengkajian permasalahan dan kerja sama dengan mitra. Tahap Kedua yaitu memberikan penyuluhan tentang gizi seimbang balita pada ibu balita tanggal 07 Mei 2025. Kegiatan diawali dengan memberikan pertanyaan pretest untuk mengetahui tingkat pengetahuan ibu balita sebelum diberikan penyuluhan. Tahap Ketiga yaitu melakukan evaluasi dengan memberikan pertanyaan posttest pada ibu balita untuk mengetahui tingkat pengetahuan ibu balita tentang gizi seimbang setelah diberikan penyuluhan. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 17 ibu balita dan 1 bidan desa. Didapatkan hasil bahwa terjadi peningkatan pengetahuan ibu balita tentang gizi seimbang balita setelah diberikan pendidikan Kesehatan. Diharapkan tenaga kesehatan meningkatkan edukasi kesehatan tentang gizi seimbang pada balita kepada masyarakat agar dapat meningkatkan tumbuh kembang balita.